Migration Processes and Their Consequences for the Labour Market in the Visegrad Group Countries – Selected Aspects - Skibiński, Andrzej (Olsztyn Economic Journal, 2017)
This article concerns the demographic problems particularly focusing on the migration processes, population ageing and their consequences for the European labour market. The author also takes into account the problem of unemployment in selected EU countries by appropriate analysis of selected labour markets in Visegrad group countries (to show their diversity and specificity). Hence, the aim of this article is to indicate the impact of the observed demographic processes (migration and changes in the population structure) on the labour market in the Visegrad countries. Applied quantitative and qualitative analyses were conducted based on data from Eurostat statistical databases with the use of demographic projections. Absolute increases of dynamics and indicators were the methods used for time series changes. The temporal scope of the analyses was largely determined by data accessibility and the fact that the Visegrhd Group countries started the process of system transformation around the same time as joining the European Union in 2004.